Characterization of Clay of the Benin Used in Ruminale Feeding. Complete Determination of the Smectites Contained in These Clays - SAGBO, VIDJANNANGNI ETIENNE; Agbahoungbata, Marielle (My University, 2015)
In this work, by the use of several physico-chemical complementary methods for the characterization of soil (diffraction of x-rays, chemical analysis, density, cationic exchange capacity, specific surfaces, mössbauer, granulometry, etc.), the smectite of the three clayey localities of Benin (Gbédji- Kotovi, Massi-Sèhouè and Zogbodomey) was notably studied. Thus, these three sites principally contain principally smectite, kaolinite and quartz in variable proportion. This smectite is a beidellite. Its chemical formula is proposed. The specific surfaces and the cationic exchange capacity of the samples are determined. For these samples, the fraction lower than 2 μm is practically beidellitic for Gbédji-Kotovi and Massi-Sèhouè (more than 82% of beidellite) and practically kaolinitic (70% of kaolinite) for Zogbodomey. So, used as additive food to ruminant, the clay of Gbédji-Kotovi and Massi-Sèhouè will induce an enteric reduction of methane more than clay of Zogbodomey.
Keywords: Clay; Characterization; Beidellite; Formula; Bénin